Bright environmental light ameliorates deficient subjective 'liking' in insomnia: an experience sampling study. Issue 4 (7th February 2018) - te Lindert, Bart H W; Itzhacki, Jacob; van der Meijden, Wisse P; Kringelbach, Morten L; Mendoza, Jorge; Van Someren, Eus J W
Abstract: Study Objectives: Altered comfort sensing and reduced gray matter volume in the orbitofrontal cortex of the brain in people suffering from insomnia disorder (ID) suggest compromised processes of motivation and hedonia. The experience sampling (ES) method was used to evaluate whether, in naturalistic conditions, people with ID differ from those without sleep complaints with respect to subjective Wanting and Liking, two major dimensions of the reward system. Since light affects brain circuits involved in affect and reward, ES was combined with ambulatory monitoring of light intensity fluctuations to evaluate their effect on subjective Wanting and Liking. Methods: Participants with ID ( n = 17, 12 females, 56.8 ± 6.5 mean ± standard deviation years of age) and matched controls without sleep complaints ( n = 18, 12 females, 57.0 ± 8.6 years of age) were probed by a smartphone alarm to log their subjective Wanting, Liking, and mood nine times a day for 7 days. Using an ambulatory light recorder, light intensity exposure was sampled simultaneously and averaged over the intervals between subsequent ES alarms. Mixed-effect models were used to evaluate how ID and varying light intensity affected subjective assessments. Results: The results indicated significantly lower subjective Liking and Wanting in people suffering from ID, particularly at low environmental light intensity. Conclusions: Wanting and Liking, rather than more commonly used mood adjectives, showed an increased sensitivity to detect deficient hedonic and reward processing in insomnia during everyday life. Deficient Liking may in part be rescued by exposure to bright environmental light.